2007
DOI: 10.1111/j.1463-1318.2007.01241.x
|View full text |Cite
|
Sign up to set email alerts
|

Sacral neuromodulation in patients with faecal incontinence: results of the first 100 permanent implantations

Abstract: Objective Faecal incontinence (FI) is a socially devastating problem. Sacral nerve modulation (SNM) has proven its place in the treatment of patients with FI. In this study, the first 100 definitive SNM implants in a single centre have been evaluated prospectively.Method Patients treated between March 2000 and May 2005 were included. Faecal incontinence was defined as at least one episode of involuntary faecal loss per week confirmed by a 3-week bowel habit diary. Patients were eligible for implantation of a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
137
2
15

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(159 citation statements)
references
References 20 publications
5
137
2
15
Order By: Relevance
“…[10] The left or right sacral foramen S3 is the nerve root most frequently chosen when implanting a temporary or permanent lead, since it leads to the best motor responses based on the experience of different research groups. [4,11] This is in accord with the anatomic origin of the innervation of the detrusor muscle and sphincter. Surprisingly S2 and S4 can occasionally elicit the best responses and the area where contact provokes responses indicative of an electrode position in S3 and S4 can vary widely among patients.…”
Section: Foramen Selectionsupporting
confidence: 62%
“…[10] The left or right sacral foramen S3 is the nerve root most frequently chosen when implanting a temporary or permanent lead, since it leads to the best motor responses based on the experience of different research groups. [4,11] This is in accord with the anatomic origin of the innervation of the detrusor muscle and sphincter. Surprisingly S2 and S4 can occasionally elicit the best responses and the area where contact provokes responses indicative of an electrode position in S3 and S4 can vary widely among patients.…”
Section: Foramen Selectionsupporting
confidence: 62%
“…5,6,7,8,9,10 SNS, which is initially used to treat urinary incontinence, was first used by Matzel et al 11 to treat FI, and a success rate of up to 75% has been reported in subsequent studies. 19 However, this invasive procedure requires two surgeries under general or local anesthesia and has specific morbidities. 20,21 PTNS is cheaper and less invasive than SNS; PTNS can also be performed without anesthesia with similar success rates.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, following the procedure we saw that voluntary contraction pressure improved in a statistically significant manner. Despite such disparity in manometric results, all authors conclude that sacral neuromodulation is a highly effective approach for the management of fecal incontinence, no matter if manometric improvement was mediated by increased rectal capacity or higher sphincteric pressures (22). Thus, we believe this technique's usefulness may be assessed using continence scales or quality of life questionnaires, with no need for anorectal manometry during the postoperative period.…”
Section: Discussionmentioning
confidence: 99%